Sistem Pakar Penyakit Kulit Pada Manusia Menggunakan Metode Certainty Factor Berbasis Web - Sri Yastita; Yohana Dewi Lulu; Rika Perdana Sari (UIN Sultan Syarif Kasim Riau, 2012)
Expert system is one part of artificial intelligence, where the system adopt human knowledge, so that the computer can do the job like an expert. There so many cases use expert system, such as skin diseases expert systems. This application is used to allow users to diagnose skin disease before further action. This application uses the methods of certainty factors, implemented using the PHP programming language and MySQL supporting data storage. This application will display the symptoms of any skin disease. The final result of the application form based on the type of disease symptoms of the selected input.Keywords: Certainty Factor , Expert System, Skin Diseases